Transitivity of The delta^n-Relation in Hypergroups - Mirvakili, Saeed; Ghiasvand, Peyman (IndoMS, 2018)
The δ^n-relation was introduced by Leoreanu-Fotea et. al.130. In this article, we introduce the concept ofδ^n-heart of a hypergroup and we determine necessary andsufficient conditions for the relation δ^n to betransitive. Moreover, we determine a family P_σ(H) ofsubsets of a hypergroup H and we give sufficient conditionssuch that the geometric space (H, P_σ(H)) is stronglytransitive and the relation δ^n is transitive.